Tissue Plasminogen Activator Release in Chronic Venous Hypertension due to Heart Failure - Keber, Irena; Keber, Dušan; Stegnar, Mojca; Vene, Nina (Thrombosis and Haemostasis, 1992)
In order to study the effects of chronic venous hypertension due to heart failure on blood fibrinolytic activity, tissue plasminogen activator (t-PA) antigen, plasminogen activator inhibitor 1 (PAI-1) antigen, t-PA activity and PAI activity were measured before and after venous occlusion of the arm for 20 min in 15 patients with right-sided heart failure, 15 patients with left-sided heart failure, and 30 control healthy subjects. Central venous pressure, measured by observing the jugular veins, was above 15 cm of the blood column in all patients with right-sided heart failure, and normal (below 8 cm) in all patients with left-sided heart failure and control subjects. There was no difference in the basal concentrations of t-PA (11.0, 10.2 and 10.8 ng/ml; all values medians) and PAI-1 antigens and their activities between right and left-sided heart failure and the control subjects. After the occlusion, t-PA antigen increased significantly less in right-sided heart failure (28.6 ng/ml) than in left-sided heart failure and the control subjects (54.5 and 45.9 ng/ml, respectively). It was concluded that the poor increase in fibrinolytic activity that had already been reported in patients with heart failure, was due to low t-PA release during occlusion and not to a high basal PAI level. It was limited to the patients with right-sided heart failure and was probably the consequence of chronic systemic venous hypertension.